Leaky nitrogen cycle in pristine African montane rainforest soil - Ruttink, T.; Cizungu-Ntaboba, L.; Roobroeck, D.; Bauters, M.; Huygens, D.; Boeckx, P. (Wiley, 2015)
Many pristine humid tropical forests show simultaneously high nitrogen (N) richness and sustained loss of bioavailable N forms. To better understand this apparent upregulation of the N cycle in tropical forests, process-based understanding of soil N transformations, in geographically diverse locations, remains paramount. Field-based evidence is limited and entirely lacking for humid tropical forests on the African continent. This study aimed at filling both knowledge gaps by monitoring N losses and by conducting an in situ 15N labeling experiment in the Nyungwe tropical montane forest in Rwanda. Here we show that this tropical forest shows high nitrate (NO3−) leaching losses, confirming findings from other parts of the world. Gross N transformation rates point to an open soil N cycle with mineralized N nitrified rather than retained via immobilization; gross immobilization of NH4+ and NO3− combined accounted for 37% of gross mineralization, and plant N uptake is dominated by ammonium (NH4+). This study provided new process understanding of soil N cycling in humid tropical forests and added geographically independent evidence that humid tropical forests are characterized by soil N dynamics and N inputs sustaining bioavailable N loss.